Tennessee's Promise: Education for All? - Tristan M. Hightower (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2019)
Access to education has been at the forefront of public policy issues over the past several years. In order to combat relatively low rates of college attainment, Tennessee legislators implemented the Tennessee Promise program. It operates by providing financial aid for any direct costs not covered by students’ grants and scholarships. Notably, the program is not applicable to four-year degree programs; students wishing to utilize the funds must attend select schools that offer certificates and associate’s degrees. Community colleges are the most popular. While a boost in community college attendance has occurred, and more people will likely graduate with an associate’s degree in the years to come, this raises an interesting question. Does restricting the choice of institution the recipients of this program have actually help to solve the education deficit in Tennessee? The number of unintended consequences suggests that the answer is no. The Tennessee Promise program is shortsighted in its goal and has serious implications for the state of education in Tennessee as a whole that future scholars should consider.
Keywords: Tennessee; Promise; Tennessee Promise; Financial Aid; Scholarship; Community College